2002
DOI: 10.1161/01.str.0000019910.90280.f1
|View full text |Cite
|
Sign up to set email alerts
|

Admission Body Temperature Predicts Long-Term Mortality After Acute Stroke

Abstract: Background and Purpose-Body temperature is considered crucial in the management of acute stroke patients. Recently hypothermia applied as a therapy for stroke has been demonstrated to be feasible and safe in acute stroke patients. In the present study, we investigated the predictive role of admission body temperature to the long-term mortality in stroke patients. Methods-We studied 390 patients with acute stroke admitted within 6 hours from stroke onset. Admission clinical characteristics (age, sex, admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(126 citation statements)
references
References 25 publications
5
114
3
4
Order By: Relevance
“…80 Even an increase of 1°F is a predictor of poorer patient outcome and is an independent factor in short-and long-term mortality rates. 82,129,156,157 The rationale for this additional injury may be related to increased metabolic demands and free radical production. Immediate treatment of the source of the fever will reduce its duration.…”
Section: Temperature Managementmentioning
confidence: 99%
“…80 Even an increase of 1°F is a predictor of poorer patient outcome and is an independent factor in short-and long-term mortality rates. 82,129,156,157 The rationale for this additional injury may be related to increased metabolic demands and free radical production. Immediate treatment of the source of the fever will reduce its duration.…”
Section: Temperature Managementmentioning
confidence: 99%
“…Elevated body temperature is also a risk factor for the hemorrhagic transformation of acute ischemic stroke when recombinant tissue-type plasminogen activator treatment is not applied to patients (15). Some studies have found that the higher and sooner the body temperature increases in the acute phase of ischemic stroke, the more severe the brain damage is likely to be; however, this correlation exists only within the first 24 h of stroke (16,17).…”
Section: A B Cmentioning
confidence: 99%
“…Side effects of hypothermia appear to occur more frequently with each degree of Celsius reduction in temperature. Temperature reductions to 35°C have been shown to be feasible and safe with surface cooling in awake, acute ischemic stroke patients, in combination with meperidine to treat shivering [46]. The ICTuS-L trial [43] found intravascular cooling to 33°C in combination with intravascular thrombolysis safe and feasible.…”
Section: Hypothermia In Ischemic Stroke: Current Clinical Literaturementioning
confidence: 99%